Trypsin Action on the Growth of Sendai Virus in Tissue Culture Cells: I. Restoration of the Infectivity for L Cells by Direct Action of Trypsin on L Cell-Borne Sendai Virus - Homma, Morio (1971)
Sendai virus grown in fertile eggs (egg Sendai) infects L cells in which the synthesis of L Sendai (grown in L cells) occurs by the one-step mechanism. L Sendai is not infectious for L cells when tested by the tube titration method although it is infectious for chick embryos. When L cells infected with egg Sendai were dispersed by trypsin and plated on a monolayer culture of L cells, the viral agents spread to the adjacent recipient cells in which the synthesis of L Sendai occurred. The newly infected L cells became infectious for L cells again by trypsin treatment. Kinetic experiments suggested that the target of trypsin is the mature virus, of L Sendai nature, just budding from the L-cell surface. By using an immunofluorescent cell-counting technique, recovery of the infectivity of L Sendai for L cells due to a direct enzymatic action of trypsin was demonstrated. Under the optimal condition, the infectivity increased 1,000-fold for L cells and 10-fold for chick embryos, and both the titers could favorably be compared. No increasing effect of trypsin was observed on the infectivity of egg Sendai. Density centrifugation studies revealed a difference between egg Sendai and L Sendai in the density. Trypsin treatment which induced the maximal enhancement of L Sendai infectivity did not affect both the densities, showing that variations of Sendai virus in the infectivity for L cells and in the density are independent types of host-controlled modification.